2019
DOI: 10.21851/obr.43.04.201912.299
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dental acid etchants in oral epithelial cells

Abstract: Phosphoric acid (P.A.; 37%) can induce necrosis on the oral mucosa and cause the ulceration of periodontal tissue. However, most studies reported are clinical case studies, with few basic science studies on oral epithelial cells. Our study aimed to investigate the effects of dental acid etchants on oral epithelial cells. After treatment with dental acid etchants for the indicated periods (0 second, 10 seconds, 30 seconds, 1 minute, and 5 minutes), cell damage, including vacuoles, pyknosis, and karyolysis, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The results of this study regarding the acid etchant application at different concentrations and durations are in complete accordance with similar studies [17,23,24]. Kim et al found that the acid etchant can damage the vacuoles and the nucleus of the cells when it is applied for 10 s or more at a concentration of 18.5% (referring to 1:2 in our study).…”
Section: Cell Viability Analysissupporting
confidence: 92%
See 3 more Smart Citations
“…The results of this study regarding the acid etchant application at different concentrations and durations are in complete accordance with similar studies [17,23,24]. Kim et al found that the acid etchant can damage the vacuoles and the nucleus of the cells when it is applied for 10 s or more at a concentration of 18.5% (referring to 1:2 in our study).…”
Section: Cell Viability Analysissupporting
confidence: 92%
“…Clinical research and studies have examined the effects of dental acid etchants on human tissues [17]. Necrosis and chemical burns were reported on the gingiva, the facial skin and the tongue [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another reason to reduce the acid concentrations used during orthodontic etching is the problems that acid can cause on oral mucosa. It was reported that inadequate rinsing of dental acid etchants or remaining dental acid etchants can cause problems, including chemical burning, irritation and inflammation, intra and extra orally 6 .…”
Section: Introductionmentioning
confidence: 99%